Seni Arsitektur Tata Ruang Bangunan Pesantren di Indonesia - Syamsuddin, Syamsuddin; Utami, Tri Wardah; Khalidiyah, Tuhfatul (Program Studi Doktor Pendidikan Agama Islam dan Program Magister Pendidikan Agama Islam, Pascasarjana Universitas Islam Negeri Sunan Ampel, 2021)
This article discusses the architectural art of pesantren in Indonesia, especially in the art of spatial planning. The spatial art of pesantren is influenced by needs and a sense of beauty. In general, the need for a pesantren room is used for worship, diniyah, school, and a resting place for students. Along with the times, pesantren began to fulfill facilities to support the needs and creativity of the students by building health rooms, sports fields, canteens, and even mini markets. In addition, architecture is also a part of art, because architecture cannot be separated from taste. The research method used in this article is library research. The research subjects were taken from several samples that could represent pesantren in Indonesia. The results of the study found six types of pesantren , namely: Type A, the physical facilities consist of mosques and kyai's houses; Type B, physical facilities in the form of a mosque, kyai's house, dormitory; Type C or salafi pesantren, physical facilities such as Type B plus school institutions; Type D or modern pesantren, pesantren have undergone a very significant transformation both in the education system and institutional elements and are very concerned about developing the talents and interests of students; Type E, namely pesantren that do not have formal educational institutions, but provide opportunities for students to study at the level of formal education outside the pesantren; and Type F or Ma'had Aly, this type is usually found in religious colleges